Studi Kasus tentang Idah dalam Tafsir Berbahasa Bugis Karya MUI Sulsel - Yusuf, Muhammad (Lajnah Pentashihan Mushaf Al-Qur'an, 2014)
This article temps to investigate Bugis Muslims ScholarsÃ¢â‚¬â„¢ view about idah in Ã¢â‚¬ËœTafesere Akorang Mabbasa OgiÃ¢â‚¬â„¢ by MUI of South Sulawesi. Idah sometimes be criticized by gender movement supporters. Form of idah in Compilation of Islamic Law (KHI) nowdays forward challange because of gender equality. Therefore, idah which formulated for women, nowdays criticed that it is not only for women, but also for men. Idah should be seen comprehensively; including texstual side, historical context, and cultural context. Texts formulated it clearly and in era of Prophet Muhammad it was for women only. Idah and ihdÃ„Âd aim both to sterilize generation line and to be momentum for self introspection and mediation for preventing divorce. The wisdom values of Bugis culture can be an alternative consideration on role of idah. Keywords: idah and ihdad, women, gender, Bugis culture, fairness, self in-trospection.